Deserting the King : the book of Judges - Beldman, David J. H., 1977- (Transformative word, 2017)
"Reading these apparently unpromising texts with Beldman, you will be instructed and challenged. In short, this is a most worthwhile study of a valuable part of the Bible.."--Cover.